Chippewa lake : a community in search of an identity - Hull, Cindy L., 1950- (Michigan State University Press, 2012)
Chippewa Lake is an idyllic waterfront community in north-central Michigan, popular with retirees and weekenders. The lake is surrounded by a rural farming community, but the area is facing a difficult transition as local demographics shift, and as it transforms from an agriculture-based economy to one that relies on wage labor. As farms have disappeared, local residents have employed a variety of strategies to adapt to a new economic structure. The community, meanwhile, has been indelibly affected by the advent of newcomers and retirees challenging the rural cultural values. An anthropologist with a background in sociology, Cindy L. Hull deftly weaves together oral accounts, historic documents, and participant surveys compiled from her nearly thirty years of living in the area to create a textured portrait of a community in flux.